PEMBINAAN PEMBUATAN SABUN CAIR CUCI PIRING DARI MINYAK JELANTAH DI KELURAHAN MULYOREJO - Arief Rahmatulloh; Mutia Devi Hidayati; Sandra Santosa (Jurnal Pengabdian kepada Masyarakat, 2024)
Mulyorejo Village is an area in the Malang which is has many home industries particularly based on food and drink which is directly proportional with the waste namely waste cooking oil. Recently, the society discharged it directly to the environment. Therefore, it is important for the people of Mulyorejo Village to obtained skills in order to processing that waste. The community service that has been done is how to make liquid dishes soap from waste cooking oil. The active ingredient is potassium hydroxide. In addition, the training was conducted through the use of reuse bottles as a substitute for plastic packaging which can later be filled through refill station. The community service was held on October 6th, 2023 with 15 participants. Based on the results of the questionnaire, it can be seen that the mean value reaches 3.84 and the mode value of each question is 4.0. Thus, it can be informed that the training participants understand, feel the benefit and satisfied with the guidance of liquid dishes soap fabrication. The training participants also received materials and tools for refilling liquid dishes soap from the community service team which could be used to produce liquid dishes soap independently.